2000
DOI: 10.1002/1521-4095(200011)12:21<1614::aid-adma1614>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterning of Oriented Zeolite Monolayers on Glass by Covalent Linkage

Abstract: The organization of micrometer‐sized zeolite (ZSM‐5) crystals into micropatterned, uniformly oriented monolayers on glass (see SEM image) is reported. The simple yet highly versatile process, which has many advantages over conventional molding and heating methods, is based on the formation of covalent links by microcontact printing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 2 publications
(2 reference statements)
2
53
0
1
Order By: Relevance
“…38,39 The first step is preparation of micropatterned monolayers of functional groups on substrates using microcontact printing 5 or photopatterning. 10,22 Figure 16a illustrates a microcontact printing-based procedure.…”
Section: Patterned Monolayer Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 The first step is preparation of micropatterned monolayers of functional groups on substrates using microcontact printing 5 or photopatterning. 10,22 Figure 16a illustrates a microcontact printing-based procedure.…”
Section: Patterned Monolayer Assemblymentioning
confidence: 99%
“…SEM images of micropatterned monolayers of zeolite microcrystals. 5,10 FIGURE 18. Structures of phenylene diisocyanate (PDI), 2-butyne-1,4-diol (BDO), and terephthalic acid bis-(2-hydroxy ethyl) ester (TBE).…”
Section: Synthesis Of Zeolite As Ordered Multi-crystal Arraysmentioning
confidence: 99%
“…However, despite a large progress made during the last several decades in the synthesis of new zeolites and the related molecular sieves [15], there have been no synthetic methods for production of uniformly aligned zeolite multi-crystal arrays. We have explored a possible post synthetic route to the production of ordered multicrystal arrays of zeolite on substrates through organization of preformed zeolite crystals with well-defined chemical linkages [16][17][18][19][20][21][22][23][24][25][26][27]. Although the above route has shown great potential, it has not yet shown the ability to control the orientation of zeolite crystals with respect to the [28][29][30][31] and the phenomenon that polyurethane sponges serve as templates for facile synthesis of large, self-supporting silicalite foams [32], we have recently demonstrated that the polyurethane films with uniformly aligned backbones can serve as the matrices for production of uniformly aligned 2D and possibly 3D arrays of zeolite crystals with uniform orientations and the nature of the polymer determines the orientation [33].…”
Section: Introductionmentioning
confidence: 99%
“…In earlier reports for selective deposition, 6,[8][9][10][11][12][13][14][15] it has been shown that patterned SAMs of OTS, can be utilized as molecular resists to create micrometer scale patterns of organosilane monolayers on the substrates for directing the deposition of thin-films. Patterned metal thin-films of Cu, 8,9 Pt, 10 3 13 has been carried out by sol-gel method.…”
Section: Introductionmentioning
confidence: 99%
“…We have also shown that patterned OTS SAMs formed by the µCP can be combined with the chemical solution deposition (CSD) for the micro-patterning of CdS thin film 14 and of zeolite particles. 15 OTS SAMs are used in these works to functionalize surfaces with organic thin films, thereby influencing the strength of the interactions of the substrate with reagents used in the sol-gel deposition process.…”
Section: Introductionmentioning
confidence: 99%